The Influence Of Chicken Feet Addition To The Nutrition Value And Organoleptic Quality Of The Corn Nugget - Hadi, Novian Swasono; Labatjo, Rahma; Setiawan, Denny Indra; Domili, Indra; Rasyid, Puspita Sukmawati; Rahmat, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Corn and chicken feet have several benefits for the development of food science and can be combined to create highly nutritious food product in the form of corn-chicken feet nugget. This study was an experiment study with three treatments and three replications. The addition of chicken feet into the corn nugget significantly contributes to the nugget’s nutritional value as well as the taste of the chicken feet corn nugget (p value = 0.000). The result of nutritional analysis revealed that the third treatment (incorporation of 30% chicken feet to the corn nugget) are of the highest nutritional value and the most favorable by the panelists.